The Insights of Genomic Synteny and Codon Usage Preference on Genera Demarcation of Iridoviridae Family - Deng, Zhaobin; Wang, Jun; Zhang, Wenjie; Geng, Yi; Zhao, Mingde; Gu, Congwei; Fu, Lu; He, Manli; Xiao, Qihai; Xiao, Wudian; He, Lvqin; Yang, Qian; et al. (Frontiers in Microbiology, 2021)
The members of the family Iridoviridae are large, double-stranded DNA viruses that infect various hosts, including both vertebrates and invertebrates. Although great progress has been made in genomic and phylogenetic analyses, the adequacy of the existing criteria for classification within the Iridoviridae family remains unknown. In this study, we redetermined 23 Iridoviridae core genes by re-annotation, core-pan analysis and local BLASTN search. The phylogenetic tree based on the 23 re-annotated core genes (Maximum Likelihood, ML-Tree) and amino acid sequences (composition vector, CV-Tree) were found to be consistent with previous reports. Furthermore, the information provided by synteny analysis and codon usage preference (relative synonymous codon usage, correspondence analysis, ENC-plot and Neutrality plot) also supports the phylogenetic relationship. Collectively, our results will be conducive to understanding the genera demarcation within the Iridoviridae family based on genomic synteny and component (codon usage preference) and contribute to the existing taxonomy methods for the Iridoviridae family.